2011
DOI: 10.1016/j.jcin.2011.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Intravascular Ultrasound Imaging on Early and Late Clinical Outcomes Following Percutaneous Coronary Intervention With Drug-Eluting Stents

Abstract: IVUS-guided stent implantation appears to be associated with a reduction in both early and long-term clinical events. Further investigation in randomized controlled trials is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(54 citation statements)
references
References 14 publications
4
50
0
Order By: Relevance
“…Recently, in nonleft main lesions, IVUSguided PCI with DES reduced both stent thrombosis and the combination of death and myocardial infarction compared with an angiographically-guided strategy. 3,4 Similar benefits also have been noted in left main lesions. In 145 propensitymatched patients undergoing unprotected left main PCI with DES from the multicenter MAIN-COMPARE (revascularization for unprotected left MAIN coronary artery stenosis: COMparison of Percutaneous coronary Angioplasty versus surgical Revascularization) registry, the 3-year mortality was lower with IVUS-guidance (4.7% versus 16.0%, Pϭ0.048).…”
Section: Article See P 562supporting
confidence: 67%
See 1 more Smart Citation
“…Recently, in nonleft main lesions, IVUSguided PCI with DES reduced both stent thrombosis and the combination of death and myocardial infarction compared with an angiographically-guided strategy. 3,4 Similar benefits also have been noted in left main lesions. In 145 propensitymatched patients undergoing unprotected left main PCI with DES from the multicenter MAIN-COMPARE (revascularization for unprotected left MAIN coronary artery stenosis: COMparison of Percutaneous coronary Angioplasty versus surgical Revascularization) registry, the 3-year mortality was lower with IVUS-guidance (4.7% versus 16.0%, Pϭ0.048).…”
Section: Article See P 562supporting
confidence: 67%
“…Increasing evidence suggests that IVUS-guidance reduces adverse events in PCI with DES in various clinical settings. 3,4 This likely relates to the preintervention assessment of appropriate stent size and interventional strategy, as well as the postintervention detection and correction of suboptimal stent deployment, such as dissections, underexpansion, geographic miss, plaque/tissue prolapse, and incomplete stent apposition. Of these, stent underexpansion most consistently has been associated with adverse events in nonleft main PCI with DES.…”
Section: Article See P 562mentioning
confidence: 99%
“…1 In the DES era, a meta-analysis including this trial and 10 registries reported that IVUS guidance may reduce ST and cardiac death after DES, although TVR rates were reduced only in complex lesion cohorts. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] The present study reports by far the largest experience with IVUS guidance of DES implantation, with a major strength being enrollment of an all-comers population. In this population, IVUS guidance was associated with lower rates of ST, MI, and ischemia-driven TLR and TVR compared with angiography guidance alone.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Nonetheless, definitive randomized trials to demonstrate whether IVUS guidance improves clinical outcomes after stent implantation have not been performed, with most prior trials being underpowered and restricted to noncomplex lesions. The benefits of IVUS after drug-eluting stent (DES) use are particularly controversial given the improved outcomes with DES compared with bare metal stents.…”
mentioning
confidence: 99%
“…Already in the past decade, several large studies have been published showing that IC imaging guidance may be important for achieving optimal DES expansion, lower malapposition rates and, consequently, better clinical outcomes, especially in complex PCI. [55][56][57][58][59] In particular, OCT is considered an established tool for the diagnosis and treatment of coronary lesions and its usefulness in improving clinical outcomes of patients undergoing PCI has been demonstrated. 60 OCT enables better visualization of the struts and the vessel wall, with a 10-fold higher axial resolution (14 μm) than intravascular ultrasound.…”
Section: Disclosuresmentioning
confidence: 99%